THE ROLE OF MEDIA TECHNOLOGIES IN DEVELOPING LISTENING AND SPEAKING SKILLS IN A FOREIGN LANGUAGE AMONG SECONDARY SCHOOL STUDENTS: THE ROLE OF MEDIA TECHNOLOGIES IN DEVELOPING LISTENING AND SPEAKING SKILLS IN A FOREIGN LANGUAGE AMONG SECONDARY SCHOOL STUDENTS. - Turegaliyeva, Nurjanar (Журнал иностранных языков и лингвистики, 2025)
In today’s computerized 21st century, we cannot even imagine teaching without technology. It’s no secret that learning foreign languages is more interesting and effective with media technologies. Technologies, including the internet, audio and video materials, interactive whiteboards, tablets, and smartphones, significantly influence the development of education.